Local inhibition of angiogenesis results in an atrophic non-union in a rat osteotomy model - Faßbender, Mirja; Strobel, C.; Rauhe, J. S.; Bergmann, C.; Schmidmaier, Gerhard; Wildemann, B. (European cells & materials, 2011)
Long bone and in particular tibia fractures frequently fail to heal. A disturbed revascularisation is supposed to be a major cause for impaired bone healing or the development of non-unions. We aim to establish an animal model, which reliably mimics the clinical situation. Human microvascular endothelial cells (HMEC-1) and primary human osteoblast like cells (POBs) were cultured with different angiogenesis-inhibitors (Fumagillin, SU5416, Artesunate and 3,5,4'-Trimethoxystilbene) released out of poly(D,L-Lactide) (PDLLA) coated k-wires and cell activity was determined. Discs containing PDLLA or PDLLA + Fumagillin/Artesunate were placed at the chorionallantoic membrane of hen eggs and the effect on vessel formation and egg vitality was observed. Tibia osteotomy was performed in rats and stabilised with K-wires coated with PDLLA + Fumagillin or with PDLLA only (control group). The healing was compared at different time points to the PDLLA control. Fumagillin and Artesunate inhibited the activity of HMEC-1 with minor effect on POBs. Artesunate caused embryonic death, whereas Fumagillin had no effects on egg vitality, but reduced the blood vessels. In the animal study all rats showed an impaired healing with reduced biomechanical stability. The Fumagillin treated tibiae had a significantly decreased callus size at day 42 and 84, less blood vessels in the early callus, a reduced histological callus size at day 10, 28 and 84, as well as an altered callus composition. This study presents a less vascularised, atrophic, tibia non-union and can be used in further investigations to analyse the pathology of atrophic non-union and to test new interventions.
Gesehen am 03.05.2022